Examining Consumers' Trust in the Food Supply Chain - CHADELLE R.H. ROBINSON; Taylor K. Ruth; R.G. "Tre" Easterly III; Fayth Franzoy; Jay Lillywhite (Journal of Applied Communications, 2020)
Consumers are concerned about the quality and safety of their food at all times during the food supply chain, but sensationalized media coverage, lack of knowledge, and recent recalls have made it difficult for consumers to trust the agricultural industry. Because trust drives risk perceptions and acceptance, it is important for agricultural communicators to understand how personal characteristics influence trust in the food supply chain. To fulfill the purpose of this study, a national quota sample of 847 responses to an online questionnaire were collected in March 2019. The results indicated respondents held a moderate level of trust toward production agriculture, food processing, food retail, and food safety regulation, with the greatest level of trust assigned to production agriculture. Trust in these sectors of the food supply chain were also positively correlated to one another. Regression models for trust in each agricultural sector were significant but only accounted for 9% of the variance in the dependent variable at most. Direct engagement in agriculture was a positive predictor in trust across all four areas, and use of social media was a negative predictor for trust. Income and gender were also found to be predictors of trust in production agriculture, food processing, food retail, and food safety regulation. The findings from this study can be used to guide future communication to increase the level of trust in the food supply chain, which would also increase consumers’ purchasing intent.
Keywords: trust; food safety; food supply chain; personal characteristics